The Classroom Teachers' Strategy of Grade V in managing Class to Enhance Students' Motivation at SD Negeri 41 Kinali - Susanti, Reka; Efrina , Gusnita; Azwar , Rica; Efendi , Nofriza (The Future of Education Journal, 2024)
This research is based on a teacher's strategy for managing the class to create a comfortable and conducive learning process and to achieve learning objectives. Therefore, this research aims to find out teachers' strategies in managing the classroom and to find out the factors that hinder classroom management at SD Negeri 41 Kinali. This research is qualitative research with a descriptive approach. Then data was collected through interviews, observation, documentation, and then data analysis was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The subjects of this research are class V teachers, PJOK teachers, PAI teachers. Based on the research results, it was found that the teacher's strategy in managing class V at SD Negeri 41 Kinali includes planning, namely compiling the Independent Curriculum module which is used as a reference in teaching. During the implementation of learning, teachers show a warm and enthusiastic attitude by showing concern and closeness to students and giving rewards to students. The inhibiting factor.